Impact of Phytoestrogens on Serum Lipids in Postmenopausal Women - Terzic, M.; Micic, J.; Dotlic, J.; Maricic, S.; Mihailovic, T.; Knezevic, N. (Geburtshilfe und Frauenheilkunde, 2012)
Objectives: The aim of the study was to assess the impact of soy- and red clover-derived isoflavones on serum lipid levels in postmenopausal women and to compare the effects to the lipid levels of healthy postmenopausal women without phytoestrogen supplementation. Materials and Methods: Blood levels of triglycerides, total cholesterol and cholesterol fractions were assessed. Measurements were performed before treatment and at 6-month intervals over a period of 18 months. The investigation included 74 healthy postmenopausal women randomized into three groups according to treatment. The first group of 23 patients received soy-derived isoflavones, the second group (26 patients) was given red clover-derived phytoestrogens, while the third control group (25 patients) received no supplements. Results: Mean triglyceride, cholesterol and LDL levels of patients in the control group were significantly higher than in both the soy and the red clover groups (p < 0.001) at all three time points, while mean values did not differ significantly between the soy and the red clover groups. The mean HDL levels of patients in the control group was significantly lower than in both the soy and the red clover groups (p < 0.001). Conclusions: Phytoestrogen supplementation had a positive metabolic effect on serum lipid levels in postmenopausal women. The impact on serum lipids levels was similar for soy and red clover.
Keywords: hormone replacement therapy (HRT); postmenopausal; phytoestrogens; soy; red clover; serum lipids